Metabolic performance and feed efficiency of black soldier fly larvae - Eriksen, Niels Thomas (Frontiers in Bioengineering and Biotechnology, 2024)
The black soldier fly (BSF), Hermetia illucens is used in entomoremediation processes, because its larvae can utilize a variety of organic residues with high efficiency. However, feed efficiencies are variable and characterized by uncertainties. Recently developed growth and metabolic performance models predict that BSF larvae have utilized 53-58% of the feed components they have assimilated, in terms of carbon equivalents, for growth throughout their lifetime when reared on chicken feed across different studies. This is termed their average net growth efficiency. The remainder carbon has been lost as CO2. However, mass balances made under similar conditions show that the weight gained by BSF larvae corresponds to only 14-48% of the feed substrates removed, the substrate conversion efficiency. Both performance indicators show even greater variability if more feed substrates are considered. Feed assimilation and growth rates, costs of growth, maintenance and larval lifespan have been shown to affect how efficiently BSF larvae convert feed into growth. The differences between average net growth efficiencies and substrate conversion efficiencies further indicate that feed is often not utilized optimally in entomoremediation processes, and that the overall yield of such processes is not determined by larval performance alone but is the result of processes and interactions between larvae, substrates, microbes, and their physical environment.The purpose of this paper is to illustrate how quantification of the metabolic performance of BSF larvae can help to improve our understanding of the role of the larvae in entomoremediation processes.